LOX/COX inhibitors enhance the antineoplastic effects of all-trans retinoic acid in osteosarcoma cell lines - Krzyzankova, Miroslava; Chovanova, Silvia; Chlapek, Petr; Radsetoulal, Matej; Neradil, Jakub; Zitterbart, Karel; Sterba, Jaroslav; Veselska, Renata (Tumor biology, 2014)
The induced differentiation of tumor cells into mature phenotypes is a promising strategy in cancer therapy. In this study, the effects of combined treatment with all-trans retinoic acid (ATRA) and lipoxygenase/cyclooxygenase inhibitors were examined in two osteosarcoma cell lines, Saos-2 and OSA-01. Caffeic acid and celecoxib were used as inhibitors of 5-lipoxygenase and of cyclooxygenase-2, respectively. Changes in the cell proliferation, matrix mineralization, and occurrence of differentiation markers were evaluated in treated cell populations at intervals. The results confirmed the capability of caffeic acid to enhance the antiproliferative effect of ATRA in both cell lines. In contrast, celecoxib showed the same effect in Saos-2 cells only. Furthermore, the extension of matrix mineralization was observed after combined treatment with ATRA and celecoxib or caffeic acid. The increased expression of osteogenic differentiation markers was observed in both cell lines after the combined application of ATRA and inhibitors. The obtained results clearly demonstrate the capability of lipoxygenase/cyclooxygenase inhibitors to enhance the antiproliferative and differentiating effect of ATRA in osteosarcoma cells, although some of these effects are specific and depend on the biological features of the respective tumor or cell line.
Keywords: kyseliny kávové; buněčná diferenciace; protinádorové látky; nádory kostí; inhibitory cyklooxygenasy; Bone Neoplasms; Tretinoin; tretinoin; pyrazoly; Humans; Cyclooxygenase Inhibitors; osteosarkom; Cell Differentiation; Pyrazoles; inhibitory lipoxygenas; proliferace buněk; Sulfonamides; lidé; Cell Line, Tumor; sulfonamidy; Caffeic Acids; Antineoplastic Agents; Lipoxygenase Inhibitors; Osteosarcoma; Cell Proliferation; nádorové buněčné linie